Facile and Selective Synthesis of 2-Substituted Benzimidazoles Catalyzed by FeCl3/ Al2O3 - Guo-Feng Chen; Xiao-Yun Dong (E-Journal of Chemistry)
2-Substituted benzimidazoles were synthesized in a single pot from aromatic aldehydes and o-phenylenediamine catalyzed by FeCl3/ Al2O3 in DMF at ambient temperature attained good yields and high selectivity.